Biochemical Taxonomy of Symbiotic Chlorella Strains from Paramecium and Acanthocystis - Kessler, Erich; Huß, Volker (Botanica Acta, 1990)
Biochemical and physiological characters of 5 symbiotic Chlorella strains, 4 of them from Paramecium (Ciliata) and one from Acanthocystis (Rhizopoda, Heliozoa), were studied. Four strains (3 from Paramecium and one from Acanthocystis) belong to the same species. This is characterized by the presence of hydrogenase, no formation of secondary carotenoids, no growth on mannitol, requirements for thiamine and vitamin B, and a G + C content of the DNA of 66.4–68.4 mol%; the limits of growth are at pH 5.5, at up to 1% NaCl, and at 26–30°C. The strains are somewhat heterogeneous in their utilization of inorganic nitrogen sources: only two of them are able to use nitrate, whereas all can grow with nitrite and ammonium. Thus, in two strains the nitrate‐reducing system — in contrast to nitrite reductase — seems to be defective. Another strain, which has been claimed to be from Paramecium, belongs to C. protothecoides. 1990 Deutsche Botanische Gesellschaft/German Botanical Society
Keywords: Biochemical taxonomy; Classification; Chlorella; Vitamin B12 requirement; Inorganic nitrogen sources; Symbiosis; Paramecium; Acanthocystis